The Effect of Social Influence, Hedonic Motivation, and Financial Literacy Moderated By Gender On The Use of Digital Wallets Among College Student - Fauziah, Annisa; Sabandi, Muhammad (Soedirman Economics Education Journal, 2024)
This study’s goals was to determine (1) the effect of social influence on the use of digital wallets, (2) the effect of hedonic motivation on the use of digital wallets among college students, (3) the effect of financial literacy on the use of digital wallets among college students, (4) find out whether gender can moderate the effect of social influence on the use of digital wallets among college students, (5) find out whether gender can moderate the effect of hedonic motivation on the use of digital wallets among college students, (6) find out whether gender can moderate financial literacy on the use of digital wallets among college students. The sampling technique was completed using purposive sampling. Data collection was carried out using questionnaires and tests. The validity test techniques used are convergent validity and discriminant validity. Data analysis uses the Moderating Regression Analysis (MRA) model. This reaserch found: (1) social influence has a positive and significant effect on the use of digital wallets among college students. (2) hedonic motivation has a positive and significant effect on the use of digital wallets among college students. (3) financial literacy has a positive and significant effect on the use of digital wallets among college students. (4) the effect between social influence and the use of digital wallets among college students is stronger for women. (5) the effect between hedonic motivation and the use of digital wallets among college students is stronger for men. (6) the effect between financial literacy and the use of digital wallets among college students is stronger for men.